The experiences of caregivers of Indigenous cancer survivors in Australia, Canada, New Zealand, and the United States: a systematic review. Issue 4 (17th December 2020) - Masa, Adam J.; Martinez-Bredeck, Helena; Butler, Tamara L.; Anderson, Kate; Girgis, Afaf; Aoun, Samar M.; Cunningham, Joan; Wakefield, Claire E.; Shahid, Shaouli; Smith, Allan B.; Garvey, Gail
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Caregivers of Indigenous cancer survivors provide critical unpaid support to survivors, yet they rarely receive information or training for this role and may themselves benefit from support services. Little is documented about the experiences of caregivers of Indigenous cancer survivors. The aim of this systematic review was to identify and aggregate qualitative research describing the experiences of caregivers of Indigenous cancer survivors in Australia, New Zealand, Canada and the United States. Methods: We systematically searched PsycINFO, PubMed, CINAHL, Embase, Scopus and Web of Science using keywords relating to Indigenous populations; caregivers; and cancer. Data were extracted from original qualitative research articles published up to March 2020. Results: From 24 full-text articles, 14 articles from 13 studies were analyzed using meta-aggregation. This highlighted key caregiver experiences relating to: the need for information about cancer and services; providing and receiving support; communication challenges and responsibilities; balancing caregiver roles and emotions; and culturally unsafe health systems and settings. Caregivers of Indigenous cancer survivors often act as mediator between Western biomedical approaches to cancer care and Indigenous peoples' holistic and family-focused views of health and wellbeing, aiming to ensure that both health professionals and the cancer survivors understand each other's perspectives and preferences for care. Caregivers expressed preferences for family-focussed rather than patient-focussed care. Culturally unsafe health care systems created barriers to optimal care. Conclusions: The findings reveal caregivers' unique experiences of caring for an Indigenous cancer survivor, and identifies several unmet needs which should be appropriately and systematically addressed. Caregivers should be regarded as co-clients with their own needs as well as co-workers with health professionals providing cancer care. Ultimately supporting caregivers will contribute to improving health outcomes for Indigenous cancer survivors.